Kontribusi Tarikan Perjalanan Kawasan Perdagangan Dan Jasa pada Jalan Menoreh Raya, Semarang - Adela Febe Andrika; Yudi Basuki (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Due to the increasing of people’s needs for goods and service, it encourages the trip attraction of commercial land uses. Menoreh Raya Street is secondary arterial street which function as commercial land use. This commmercial land use conduce the trip attraction that contribute to traffic flows. Therefore, the calculation of trip attraction’s contribution is needed to anticipate the problem in future. The purpose of this study is to know the contribution of commercial land use’s trip attraction on one corridor and the contribution of commercial land use’s trip attraction per type. The methods that used in this study are calculate the trip attraction and the contribution of trip attraction. The results show that this commercial land use contributes 9,75% to traffic flows of Menoreh Raya Street on peak hour. The biggest contribution is attracted by variety store by 24,93%, high-turnover (sit-down) restaurants by 21,09%, and quality restaurant by 10,62%. Menoreh Raya Street’s function as connection between downtown and sub-urban makes the traffic flows are dominated by go home after work activity. Moreover, people tends to buy some daily needs and dinner on evening’s peak hour. This study could be used to know the contribution of traffic volume that attracted by commercial land use on secondary arterial street’s traffic flows that has same characteristic with Menoreh Raya Street. The contribution of trip attraction is useful to anticipate the commercial land use’s trip attraction that affect the increasing of street load and traffic jam.